2016
DOI: 10.1515/cpe-2016-0005
|View full text |Cite
|
Sign up to set email alerts
|

Influence of different factors on momentum transfer in mechanically agitated multiphase systems

Abstract: A comparative analysis concerning the influence of different factors on momentum transfer in mechanically agitated systems was carried out on the basis of experimental results for solid-liquid, gas-liquid and gas-solid-liquid systems. The effects of the impeller -baffles system geometry, scale of the agitated vessel, type and number of impellers and their off-bottom clearance, as well as physical properties of the multiphase systems on the critical impeller speeds needed to produce suspension or dispersion, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…RT experiments consume more energy with the exception of no baffle experiment, where PBT has a higher value of power consumption compared to the RT experiment something that is confirmed from the literature. 40 , 41 It should be mentioned that PBTU is the same with PBT because all mixed flow experiments occur in upward trending.…”
Section: Resultsmentioning
confidence: 99%
“…RT experiments consume more energy with the exception of no baffle experiment, where PBT has a higher value of power consumption compared to the RT experiment something that is confirmed from the literature. 40 , 41 It should be mentioned that PBTU is the same with PBT because all mixed flow experiments occur in upward trending.…”
Section: Resultsmentioning
confidence: 99%
“…The Rushton turbine was not recommended to biological processes with microorganisms and processes which are very sensitive to the shear stress. At another research work by Cudak et al [79] a comparative analysis based on experimental data concerning the impact of the impeller geometry and baffles geometry, number and shape of impellers, the scale of the agitated tank, as well as their off-bottom clearance and properties of the multiphase systems on the critical impeller speeds, were investigated. The authors conclude that in order to generate dispersion or suspension, energy consumption and gas hold-up have to be considered in parallel in order to enable appropriate conditions to drawdown or suspended particles, as well as to disperse small and large air bubbles in liquids.…”
Section: Gas-liquid and Gas-liquid-liquid Systemmentioning
confidence: 99%
“…The simulation results showed that flow pattern and dimensionless velocity distribution are related to Reynolds number and regime type without change values in the turbulent regime. The lowest drop of total power number for single and parallel configuration of the impellers was observed in laminar regime [5,6,78,79,164]. A large number of researchers have performed numerical simulations to examine the impact of impeller geometry on the mixing process in order to find optimal configuration, low mixing time or low power consumption [165][166][167].…”
Section: The Effect Of Impellersmentioning
confidence: 99%
“…Many empirical correlations were presented for power consumption (Nagata, 1975;Stręk, 1981), heat transfer (Kuncewicz, 2012;Stręk, 1981) and mass transfer (Harnby et al, 1997), as well as for multiphase systems (Kamieński, 2004;Tatterson, 1991). Recently, experimental studies have been developed on momentum transfer (Cudak et al, 2016), power consumption (Major-Godlewska and Karcz, 2018), heat transfer (Petera et al, 2017;Rosa et al, 2020), multi-phase system production (Cudak, 2016, Cudak et al, 2019Kiełbus-Rąpała et al, 2019), gas hold-up (Busciglio et al, 2017;Cudak, 2020;Lee and Dudukovic, 2014) and mass transfer (Kracik et al, 2020;Petricek et al, 2018).…”
Section: Introductionmentioning
confidence: 99%